1999
DOI: 10.1161/01.str.30.3.580
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Guide to Assess the Role of Lower Limb Extensor Overactivity in Hemiplegic Gait Disorders

Abstract: Background and Purpose-The aim of this study was to assess the role of knee and ankle extensor overactivity in the hemiplegic gait observed in stroke victims and to propose a clinical guide for selecting patients before treatment of a supposed disabling spasticity. Methods-A standardized physical examination procedure was performed in 135 consecutive stroke patients. All patients were able to walk without human assistance. The period after stroke ranged from 3 to 24 months (mean, 11.5Ϯ7.25 months). Spasticity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 27 publications
(31 reference statements)
3
30
0
1
Order By: Relevance
“…Following stroke, withdrawal reflexes in the upper-limb have been shown to produce an abnormal spatial distribution of torque (Dewald et al 1999) which was similar in nature to the constrained torque synergies seen during volitional arm movements (Dewald et al 1995). In the hemiparetic lower limb, the facilitation of quadriceps motoneurons following stimulation of the common peroneal nerve (Marque et al 2001b) and the facilitation of rectus femoris in the current study may reflect the abnormal activation of the quadriceps prior to and during the swing phase of gait (Yelnik et al 1999;Den Otter et al 2006).…”
Section: Functional Implicationssupporting
confidence: 59%
See 1 more Smart Citation
“…Following stroke, withdrawal reflexes in the upper-limb have been shown to produce an abnormal spatial distribution of torque (Dewald et al 1999) which was similar in nature to the constrained torque synergies seen during volitional arm movements (Dewald et al 1995). In the hemiparetic lower limb, the facilitation of quadriceps motoneurons following stimulation of the common peroneal nerve (Marque et al 2001b) and the facilitation of rectus femoris in the current study may reflect the abnormal activation of the quadriceps prior to and during the swing phase of gait (Yelnik et al 1999;Den Otter et al 2006).…”
Section: Functional Implicationssupporting
confidence: 59%
“…Biomechanical simulations investigating potential muscular contributions to this impaired knee flexion have revealed that it may be attributed to abnormal activation of the quadriceps (Piazza and Delp 1996;Riley and Kerrigan 1998;Goldberg et al 2004). Indeed, analysis of muscle activity during hemiparetic gait has revealed that abnormal activation of the quadriceps prior to and during the swing phase appears to be consistent across subjects (Yelnik et al 1999;Den Otter et al 2006). The goal of this study was to determine if there is evidence for a spinal contribution to this abnormal pattern of muscle activity following stroke.…”
Section: Introductionmentioning
confidence: 99%
“…In the present, population-based study, it is unlikely that we have underestimated the prevalence of spasticity: in the MAS, spasticity is equated with any measurable increase in velocity-dependent resistance to passive stretch – whether reflex mediated or not. However, regardless of the cause, the exact influence of spasticity on disability in stroke patients is difficult to assess, because the degree of spasticity may change with body position and with the task being performed [28]. Only 8% of the patients in the present study reported muscle stiffness, further underscoring the low prevalence of increased muscle tone in our cohort.…”
Section: Discussionmentioning
confidence: 67%
“…Gait is a complex activity that relies on navigation and rhythmic motor activity of the 2 lower limbs and requires a good balance. In brain-damaged patients, the level of gait performance can be affected by many factors, such as impaired equilibrium (difficulty in controlling the orientation and/or stabilization of the body with respect to gravity), tone disorders, 33 and strength deficits. 34 For this reason, and in agreement with most other authors, 5-9,13,30,33-35 we chose to separate posture and gait assessments.…”
Section: Benaim Et Al Standardized Assessment Of Postural Control In mentioning
confidence: 99%